2006
DOI: 10.1159/000090432
|View full text |Cite
|
Sign up to set email alerts
|

Combining 2nd-Trimester Maternal Serum Homocysteine Levels and Uterine Artery Doppler for Prediction of Preeclampsia and Isolated Intrauterine Growth Restriction

Abstract: Aim: To evaluate the efficacy of a combined 2nd-trimester maternal serum homocysteine and uterine artery Doppler screening at 20 weeks of gestation for complications of pregnancy: preeclampsia, isolated intrauterine growth restriction (IUGR), placental abruption, and stillbirths. Methods: Consecutive singleton pregnancies without previous risk factors who had homocysteine measured as part of a serum-screening program for trisomy 21 had uterine artery Doppler performed. Sensitivity, specificity, positive and ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
1
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 72 publications
1
18
1
1
Order By: Relevance
“…In contrast, other studies detected no differences in midtrimester maternal circulating level of homocysteine between women who developed preeclampsia and normal pregnant women 15,[18][19][20] .…”
Section: Discussionmentioning
confidence: 74%
“…In contrast, other studies detected no differences in midtrimester maternal circulating level of homocysteine between women who developed preeclampsia and normal pregnant women 15,[18][19][20] .…”
Section: Discussionmentioning
confidence: 74%
“…A prospective study assessed uterine artery Doppler measurements at 20 weeks gestation in combination with midtrimester maternal serum homocysteine levels in the prediction of pre-eclampsia. Sensitivity for predicting pre-eclampsia of 60% was observed, with a false-positive rate of 3% (Onalan et al, 2006).…”
Section: Combination Of Biochemical Markers With Uterine Artery Dopplmentioning
confidence: 93%
“…Earlier, a case-control study reported increased homocysteine levels at early midtrimester in women with subsequent severe and non-severe pre-eclampsia (Cotter et al, 2003). In contrast, other studies detected no difference in midtrimester homocysteine serum levels between women who developed pre-eclampsia and controls (Yu et al, 2004;Onalan et al, 2006;D'Anna et al, 2004). The contradictory results undermine the potential of homocysteine as a marker for subsequent pre-eclampsia.…”
Section: Homocysteinementioning
confidence: 96%
“…Consequently, a number of studies have evaluated the relationship between tHcy and pregnancy outcome to find out whether increased tHcy is associated with adverse pregnancy outcomes, and if so, whether the relationship is causal. Increased tHcy has been associated with an increased risk of preeclampsia (2)(3)(4)(5)(6)(7)(8)(9)(10), intrauterine growth restriction (3,7 ), abruptio placenta (7 ), stillbirth (2,7 ), and miscarriage (11 ). Systematic reviews generally support the positive association between tHcy and placenta-mediated conditions, including pregnancy loss, preeclampsia, and abruption (1,12,13 ).…”
mentioning
confidence: 98%